Integrating Islamic Fintech into Islamic Social Finance to Revive the Going Concern of MSMEs in the COVID-19 Era - Umar Habibu Umar; Muhammad Aminu Umar (Global Review of Islamic Economics and Business, 2022)
This study seeks to propose a model that integrates Islamic social finance and Islamic fintech to revive MSMEs' going concerns during the COVID-19 pandemic in Nigeria. The study applies content analysis and a multidisciplinary literature review. This study proposes a model that integrates Islamic social finance instruments (such as zakat [Islamic compulsory tax], waqf [Islamic endowment], Islamic microfinance and sadaqat [voluntary charity]) and Islamic fintech platforms (P2P and crowdfunding) that could enable MSMEs to obtain funds to revitalize their going concerns by engaging in various Islamic-based contracts, such as musharakah (equity partnership), murabahah (the cost-plus sale contract), mudarabah (trust partnership), ijarah (lease contract), musharakah mutanaqisah (diminishing equity partnership), qard al-hasan (free interest loan), salam (forward financing transaction), etc. The provision of adequate finance using the proposed integrated model is expected to revitalize the MSMEs' going concerns, which can contribute to the country's economic growth and development. Despite the study's contribution by inventing an Islamic-based model for reviving the MSMEs' going concerns in Nigeria, it is conceptual without empirical validation. Hence, future studies should empirically explore the feasibility of the proposed integrated model. The implications of the findings indicate the need to provide motivational regulations for establishing Islamic fintech companies. There is also a need to provide effective technological applications that ensure the selection of only eligible beneficiaries.